역사과 민주시민 교육의 성과와 과제 - 2007개정 교육과정 이후 ‘한국사’ 영역을 중심으로 - 문경호(Mun, Gyung-ho) (교과교육학연구, 2021)
이 글에서는 최근 역사교육계에서 강조되는 민주시민 교육의 본질적인 문제에 접근하기 위해 2007개정 교육과정 이후 중고등학교 한국사 영역에서 민주주의 관련 내용이 어떻게 변화되어 왔으며, 앞으로 해결해야 할 과제가 무엇인지 살피려 하였다. 민주시민 양성은 학교 교육을 통해 이루어야 하는 교육의 본질적인 목표이다. 그런 의미에서 역사교육에서의 민주시민 교육은 민주화 운동에 대한 지식 습득과 함께 민주시민으로 성장하기 위한 가치와 태도를 함양할 수 있도록 설계되어야 한다. 민주주의와 관련된 현대사 교육을 강화시키는 데에 중점을 두기보다 역사적 사실을 학습하는 과정에서 민주주의적 가치가 존중되고, 내면화되는 경험을 하도록 해야 한다. 또한, 학생들이 역사 속에서 여러 시기의 다양한 사람들을 만나며, 인문학적 상상력과 통찰력을 키울 수 있도록 내용이 조직되어야 한다. This article looked into the changes in Korean history subject in middle and high schools since the curriculum revision on 2007, and future tasks needed to be addressed to better understand the essential issues of democratic citizens education that has been particularly emphasized in recent history education. Cultivating democratic citizens is an essential goal to achieve with school education. In this respect, the democratic citizens education in history subject should be designed to obtain the virtue and knowledge to grow as democratic citizen based on the historic knowledge in multiple eras, as well as acquiring the knowledge on the democratic movement. It should be focused on putting value on respecting the democratic virtue and internalizing the experience in the course of studying the historic facts rather than concentrating on strengthening the contemporary history of democracy. In addition, the contents should be organized for the students to grow the liberal artistic imagination and insights, learning about various events and people in history. KCI Citation Count: 0